2013
DOI: 10.1007/s40003-012-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Maize and Faba Bean for Silage Under Swedish Climate Conditions

Abstract: Cultivation of forage maize is increasing in Sweden. Sole maize is low in protein and supplementation of protein feed is needed. This study investigated whether forage maize and legumes can be intercropped in a system suitable for farmers (simultaneous sowing and harvest) under Swedish climate conditions, and whether intercropping maize and faba bean improves the forage quality compared with sole maize. Two field experiments were performed in which maize intercropped with faba bean (Vicia faba L.) in alternate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
2
25
2
Order By: Relevance
“…Higher concentration of volatile fatty acids at 40% M:60% S intercropping ratio and soybean monoculture in this study could be explained by higher pH (Table 3) and lower WSC content (Table 4). These results were in contrast to those reported by Stoltz et al (2013) who found a higher concentration of butyric acid in corn monoculture compared with corn–faba bean ( Vicia faba L.).…”
Section: Resultscontrasting
confidence: 99%
“…Higher concentration of volatile fatty acids at 40% M:60% S intercropping ratio and soybean monoculture in this study could be explained by higher pH (Table 3) and lower WSC content (Table 4). These results were in contrast to those reported by Stoltz et al (2013) who found a higher concentration of butyric acid in corn monoculture compared with corn–faba bean ( Vicia faba L.).…”
Section: Resultscontrasting
confidence: 99%
“…Intercrops compete with each other for resources such as light, water and nutrients, and it is not always easy to control the competitive interactions between the two crops due to their different rooting ability, canopy structure and nutrient requirements. Studies of intercropping maize in North Europe are scanty (Stoltz and Nadeau 2014;Stoltz et al 2013). Under similar climatic conditions, reported effects of intercropping cereals with catch crop on cereal yields are both positive (Hauggaard-Nielsen et al 2001) and neutral/negative (Kankanen and Eriksson 2007;Thorsted et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Maize crop can produce high yield in a TÜRK TARIM ve DOĞA BİLİMLERİ DERGİSİ TURKISH JOURNAL of AGRICULTURAL and NATURAL SCIENCES single cut (Serbester et al, 2015) and is easy to ensile due to its water soluble carbohydrate (WSC) content. It also has high energy value as ruminant feed (Stoltz et al, 2013;Geren et al, 2008). However, the most important handicap of maize is definitely its low crude protein (CP) content that is around 6-7% of its dry matter (DM) base.…”
Section: Introductionmentioning
confidence: 99%
“…So not decreasing maize plant density in intercrop may be a good way in order to keep high silage yield produced. The fact remains that; there have been many studies that individual crop of any intercrop systems were sown or harvested at different time points (Stoltz et al, 2013). However, this is not applicable for practice for silage production system.…”
Section: Introductionmentioning
confidence: 99%